Climate Mitigation And Waste Management In The Tourism Industry For A Sustainable Ecosystem - Wiratama, I Gusti Ngurah Made; Wijaya, I Made Wahyu; Kenedy, Fransiskus Vebrian (Lembaga Penelitian dan `Pengabdian Kepada Masyarakat (LPPM), 2024)
Climate is one of the primary factors that influence international tourism. Most international travelers are interested in visiting nations with a distinct and more agreeable environment. This study aims to define the responses of tourism industry to face the climate change impacts through mitigation initiatives. Climate is a tourism resource that defines the viability of areas to sustain tourist activities, influences tourism demand, and affects operating expenses such as heating and cooling, artificial snow prices, and water and irrigation availability. Some mitigation efforts and waste management for the tourism industry to facing the climate change impacts are concerning on energy efficiency, resources and product supply, transportation, waste and wastewater management, and human resources development and awareness.